PKM Pelatihan Penilaian Akademik Untuk Guru-Guru SD/SMP/SMA/Sederajat Di Kabupaten Sidrap: Indonesia - Sudarmanto Jayanegara; Asham Bin Jamaluddin; Muhammad Ansarullah; Aminuddin; Ismail Aqsha; Dary Mochamad Rifqie; Haristo Rahman (Sakura Digital Nusantara, 2023)
Academic assessment is an evaluation process or learning outcomes to measure student learning progress and achievements in the context of formal education, using established methods, instruments and criteria, as well as providing relevant feedback. In improving the quality of education in schools, it is necessary to have an effective and objective academic assessment system which is an important element in improving the assessment system. Therefore, this study aims to provide training on how to assess learning outcomes or academic results for SD/SMP/SMA/equivalent teachers in Sidrap District. The method of implementing the service is lectures, discussions, and the practice of using the instruments provided. The results of the evaluation of practicing the instruments obtained are that teachers get a simple and easy academic assessment system when processing students' grades and teachers will be able to make assessment instruments according to the 2013 curriculum standards. This service in the form of training is expected to provide great benefits for teachers -teachers in SIdrap District in an effort to increase their understanding of good academic assessment and can improve the quality of assessment in schools.